The future of African peace operations From the Janjaweed to Boko Haram - De Coning, Cedric; Gelot, Linnéa; Karlsrud, John (Africa Now, 2016)
Facing threats ranging from Islamist insurgences to the Ebola pandemic, African regional actors are playing an increasingly vital role in safeguarding peace and stability across the continent. But while the African Union has demonstrated its ability to deploy forces on short notice and in difficult circumstances, the challenges posed by increasingly complex conflict zones have revealed a widening divide between the theory and practice of peacekeeping. With the AU 's African Standby Force becoming fully operational in 2016, this timely and much-needed work argues that responding to these challenges will require a new and distinctively African model of peacekeeping, as well as a radical revision of the current African security framework. The first book to provide a comprehensive overview and analysis of African peace operations, The Future of African Peace Operations gives a long overdue assessment of the ways which peacekeeping on the continent has evolved overthe past decade. It will be a vital resource for policy makers, researchers and all those seeking solutions and insights into the immense security challenges which Africa is facing today.